A Thorough Assessment of the Causal Relationship from Tourist Satisfaction to Destination Loyalty: A Study in Tra Vinh - Huynh, Quang Linh (International Journal of Economics and Financial Issues, 2018)
Tourists' destination loyalty plays a vital role in developing tourism at local tourism attractions; it is however conditional on the tourists' satisfaction with destination, which is while determined by several other contingent factors. This study applies the Heckman two-stage method to examine the impact of tourists' destination satisfaction on their loyalty to destination. The findings offer statistical support for the effects of tourism environment, tourism staff, services price, tourism transportation facilities, tourism service, tourism infrastructure and socio-cultural environment on tourists' destination satisfaction, but no statistical evidence on the influence of lodging amenities on tourists' satisfaction with destination. The Heckman two-stage results provide evidence on the existence of sample selection bias in the research model. This research sheds light on the casual correlation from tourists' destination satisfaction to their destination loyalty with the intervention of sample selection bias. Keywords: Tourism development; Tourist satisfaction; Tourist loyalty JEL Classifications: L83, O53, Z32